Evolutionary Analysis of MIKCc-Type MADS-Box Genes in Gymnosperms and Angiosperms - Chen, Fei; Zhang, Xingtan; Liu, Xing; Zhang, Liangsheng (Frontiers in Plant Science, 2017)
MIKCc-type MADS-box genes encode transcription factors that control floral organ morphogenesis and flowering time in flowering plants. Here, in order to determine when the subfamilies of MIKCc originated and their early evolutionary trajectory, we sampled and analyzed the genomes and large-scale transcriptomes representing all the orders of gymnosperms and basal angiosperms. Through phylogenetic inference, the MIKCc-type MADS-box genes were subdivided into 14 monophyletic clades. Among them, the gymnosperm orthologs of AGL6, SEP, AP1, GMADS, SOC1, AGL32, AP3/PI, SVP, AGL15, ANR1, and AG were identified. We identified and characterized the origin of a novel subfamily GMADS within gymnosperms but lost orthologs in monocots and Brassicaceae. ABCE model prototype genes were relatively conserved in terms of gene number in gymnosperms, but expanded in angiosperms, whereas SVP, SOC1, and GMADS had dramatic expansions in gymnosperms but conserved in angiosperms. Our results provided the most detailed evolutionary history of all MIKCc gene clades in gymnosperms and angiosperms. We proposed that although the near complete set of MIKCc genes had evolved in gymnosperms, the duplication and expressional transition of ABCE model MIKCc genes in the ancestor of angiosperms triggered the first flower.